Comparative Evaluation Of Measurement Of Gingival Thickness Using Different Techniques (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Gingival thickness is a crucial factor that is that is considered throughout the process of treatment. The techniques for measurements of gingival thickness are mainly divided into two categories qualitative and quantitative measurements. The periodontal probe method is the most commonly used in clinical practice. In recent years CBCT can not only be used to evaluate the hard tissue but also to assess the thickness of soft tissue with some modifications in technique.Objectives:The objective of this study was to compare and evaluate gingival thickness using five different measurement techniques. Methodology: A total of ten patients were included in this study. The procedure was explained to each patient and informed consent was obtained. Measurements of gingival thickness were made in the maxillary central incisors. The individuals in the study were all in good general health and had no crowding of teeth. The gingival thickness was measured using five distinct methods named as Transparency Method, Paralleling technique, Transgingival Probing, CBCT method and Digital superimposition method. Patients were categorized into five groups based on different techniques of measurement of gingival thickness.Results:One-way ANOVA (Analysis of variance) is a statistical method for comparing the means of two or more samples. In our study One Way, ANOVA test showed that there is no statistical difference between all the techniques. Conclusion: No significant difference between different techniques. However, CBCT has come out to be most effective in terms of being non-invasive method and accuracy. The most expensive method was Digital superimposition followed by CBCT and the most invasive method was transgingival probing.